2011
DOI: 10.1126/science.1197397
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Modern Heat Transfer to the Arctic by Warm Atlantic Water

Abstract: The Arctic is responding more rapidly to global warming than most other areas on our planet. Northward-flowing Atlantic Water is the major means of heat advection toward the Arctic and strongly affects the sea ice distribution. Records of its natural variability are critical for the understanding of feedback mechanisms and the future of the Arctic climate system, but continuous historical records reach back only ~150 years. Here, we present a multidecadal-scale record of ocean temperature variations during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
352
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(395 citation statements)
references
References 33 publications
27
352
0
3
Order By: Relevance
“…Parts of the Antarctic Peninsula, including the WAP, are already experiencing the greatest increase in mean annual atmospheric temperature on Earth (Chapman and Walsh, 2007;Clarke et al, 2007;Solomon et al, 2007;Smale and Barnes, 2008), and temperatures at the seafloor in the Southern Ocean are predicted to rise by as much as 0.7°C at abyssal depths and 1.7°C at bathyal depths by 2100 ( Table 2). Field and modeling studies have also revealed rapid atmospheric and surface-water warming in the Arctic Ocean during recent decades (Overland et al, 2004;Spielhagen et al, 2011). Bathyal Arctic waters are following this rapid warming trend (Soltwedel et al, 2005), and temperatures at both bathyal and abyssal depths could increase by as much as 0.1-3.7°C relative to present-day temperatures by 2100 (Table 2; Figure 2).…”
Section: The Polar Deep Seasmentioning
confidence: 99%
“…Parts of the Antarctic Peninsula, including the WAP, are already experiencing the greatest increase in mean annual atmospheric temperature on Earth (Chapman and Walsh, 2007;Clarke et al, 2007;Solomon et al, 2007;Smale and Barnes, 2008), and temperatures at the seafloor in the Southern Ocean are predicted to rise by as much as 0.7°C at abyssal depths and 1.7°C at bathyal depths by 2100 ( Table 2). Field and modeling studies have also revealed rapid atmospheric and surface-water warming in the Arctic Ocean during recent decades (Overland et al, 2004;Spielhagen et al, 2011). Bathyal Arctic waters are following this rapid warming trend (Soltwedel et al, 2005), and temperatures at both bathyal and abyssal depths could increase by as much as 0.1-3.7°C relative to present-day temperatures by 2100 (Table 2; Figure 2).…”
Section: The Polar Deep Seasmentioning
confidence: 99%
“…The core from the Fram Strait spans approximately the last 2000 yr. The age model for core MSM05/05-712-1 is based on five AMS 14 C age measurements (Spielhagen et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Increased input of ocean heat from the Pacific (Shimada et al 2006;Woodgate et al 2006) and the Atlantic (Spielhagen et al 2011) are also contributing to ice melt. Finally, reductions in summertime cloud cover (the only season in which clouds have a net cooling effect in the Arctic) may have contributed to record sea-ice retreat in 2007 (Kay et al 2008).…”
Section: Sea-icementioning
confidence: 99%
“…The Atlantic waters that enter the Arctic Ocean at depth are now unusually warm and are enhancing heat flux to the surface and potentially contributing to sea-ice melt (Spielhagen et al 2011). The Barents Sea has warmed considerably at depth, tracking a strong phase of the Atlantic Multi-decadal Oscillation (Levitus et al 2009).…”
Section: Ocean Circulationmentioning
confidence: 99%
See 1 more Smart Citation